An Analysis Of Inventory Accounting At Shoe And Sandal Store (Kedai Ganteng) In Penurunan Of Bengkulu City - Owen, Delta; Soleh , Ahmad; Kurniawan, Kimas (Journal of Multidisciplinary Research, 2025)
In a trading company, one of the most important accounting systems is the inventory accounting system. Because it aims to manage financial data and information about inventory from various users, both internal and external to the company. Inventory is goods available for sale in ordinary business activities. In the production process for the sale. In the form of materials or equipment to be used in the production process or provision of services. The purpose of this study is to determine inventory accounting in shoe and sandal Store (Kedai Ganteng) of Bengkulu City. The technique used in this study is a comparative descriptive research design. Comparative descriptive research is intended for assessments that compare the conditions of one or more variables in two or more different samples, or two different times. In general, the basis for recording used by shoe store entrepreneurs in Bengkulu City is cash basic. Shoe store entrepreneurs have not implemented the concept of the Procedure for recording the cost of finished goods sold Because they do not use a general journal, they only use basic manual recording. Shoe store entrepreneurs have implemented the concept of the Procedure for recording the cost of goods purchased. The conclusion of this study is that the application of accounting compiled by shoe and sandal Store (Kedai Ganteng), Bengkulu City, is not in accordance with the basic concept of accounting according to Mulyadi .